Experiências de racismo e o desenvolvimento da identidade étnico-racial em crianças negras e brancas - Moreira Primo, Ueliton Santos (2020)
Racism is a widespread experience in the lives of black Brazilian citizens that begins in childhood. As a psychosocial stressor, racism compromises developmental trajectories through several components, including effects on psychological and physical well-being. Even so, little is known about the experiences of racism that children face in their lives and about the development of ethnic-racial identity in this very important phase of life. The objective of this dissertation is to analyze the impacts of racism on children, specifically on their school trajectories, on the development of ethnic-racial identity and on occurrences of racism and racial discrimination. To answer this objective, the dissertation was organized in five chapters. The first chapter is a theoretical study, which aimed to make brief conceptual and historical presentations on racism in Brazil, bringing contemporary elements from these discussions, such as the whitening ideology and the myth of racial democracy. The next four chapters are in article formats. The first article is a systematic review of the literature on the effects of racism on the school trajectory of Brazilian children. The second article is a study that analyzes the effects of age and skin color on the development of ethnic-racial identity and the perception of the social value of black and arm in 136 children. The third article describes an empirical study that sought to discuss the occurrences and frequencies of racism and discrimination perceived by 60 children, including the contents, the perpetrators and the contexts in which it occurs. Finally, in the fourth and last article, the emotional meanings of the experience of racism at school for ten black children were analyzed. The main results of this dissertation demonstrate that the occurrence of situations of racism is a reality that is strongly present in the lives and daily lives of children, especially in the school context. As a result, exposure to racism and racial discrimination contributes to the development of the less positive ethnic-racial identity and affects the psychological, emotional, physical and social well-being of child victims. The dissertation concludes by defending that anti-racist measures are urgently undertaken at school and in the whole of society, for this, some considerations are made suggesting how, especially, the school community should get involved in overcoming racism.